Understanding the New Testament use of the Old Testament: forms, features, framings, and functions - Huffman, Douglas S. (Baker Academic, a division of Baker Publishing Group, 2024)
"This up-to-date introduction looks not just at the forms but also the functions of the New Testament's use of the Old Testament"--